Controle de vassourinha-de-botão em diferentes estágios de desenvolvimento no Amazonas - Teixeira, Anne Geiza Tamer (2020)
In the state of Amazonas, one of the dominant weed species in native grassland areas is Spermacoce verticillata L., known in the region as button broom. This study aimed to evaluate the efficiency of glyphosate in the control of button broom plants, in different stages of growth. The experiment was conducted in the experimental area of the Institute of Exact Sciences and Technology-ICET. The experimental design used was the entirely randomized, 5 x 4 factor arrangement (five growing doses of the herbicide glyphosate, namely: 0; 960, 1.920, 2.880 and 3.840 g ha-1 of e.a.; and four stages of plant growth: 60, 90, 120 and 150 days after emergence), with 10 repetitions, in which each repetition was represented by a plant. The phytotoxicity assessments were made at 7, 14, 21, 28, 35 and 42 days after the application of the herbicide, through the adapted model of the European Weed Research Community (EWRC) Conceptual Scale. At 42 days after application (DAE) of the herbicide, at the time of discarding the experiment, the plants were cut close to the ground, to measure the height and determine the dry matter of the aerial part. The drying took place in a forced air circulation oven at a temperature of 60°C until the plants reached constant weight. The data collected were submitted to analysis of variance by the F test, and their means compared by the Tukey test at 5% probability. According to the results obtained, the plants of S. verticillata are more susceptible to the action of the herbicide from 60 to 90 DAE. The doses of 960, 1,920 and 2,880 g ha-1 of e.a of glyphosate applied to plants with 60 to 90 DAE controlled 100% of the plants. For a greater efficiency in the application of the herbicide, and considering a lower cost in the control of the weeds and less damage to the environment, it is recommended to adopt the dose 960 g ha-1 of glyphosate e.a., applied within 90 days after the emergence of S. verticillata.